2010
DOI: 10.1021/je1005196
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Binary Mixtures of Tetrahydropyran with Anilines at 308.15 K

Abstract: Excess molar volumes, V E , excess molar enthalpies, H E , speeds of sound, u, and vapor-liquid equilibrium data of tetrahydropyran (1) + aniline or N-methylaniline or 2-methylaniline (2) binary mixtures have been measured over the entire mole fraction range at 308.15 K. Speeds of sound and vapor-liquid equilibrium data have been utilized to predict isentropic compressibility changes of mixing, κ S E

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This paper reports C P E data of pyrrolidin-2-one or 1-methylpyrrolidin-2-one (1) + o -, m -, or p -chlorotoluene (2) binary mixtures at 293.15 K, 298.15 K and 303.15 K. A literature survey showed that C P E data of these mixtures are not reported in the literature. Graph theory (which in turn deals with constituent of mixtures) has been successfully employed to determine excess molar volumes, V E , excess molar enthalpies, H E , excess Gibbs free energies, G E , and excess isentropic compressibilities, κ S E data of liquid mixtures. In this study, a connectivity parameter of the third degree of a molecule, 3 ξ which in turn deals with topology of a molecule (Graph theory) has been utilized to predict C P E data of the investigated mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…This paper reports C P E data of pyrrolidin-2-one or 1-methylpyrrolidin-2-one (1) + o -, m -, or p -chlorotoluene (2) binary mixtures at 293.15 K, 298.15 K and 303.15 K. A literature survey showed that C P E data of these mixtures are not reported in the literature. Graph theory (which in turn deals with constituent of mixtures) has been successfully employed to determine excess molar volumes, V E , excess molar enthalpies, H E , excess Gibbs free energies, G E , and excess isentropic compressibilities, κ S E data of liquid mixtures. In this study, a connectivity parameter of the third degree of a molecule, 3 ξ which in turn deals with topology of a molecule (Graph theory) has been utilized to predict C P E data of the investigated mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…This has greatly stimulated the need for extensive information about thermodynamic properties of mixtures containing cyclic ether. In our systematic investigations of thermodynamic properties of binary and ternary mixtures containing cyclic ether, excess molar volumes, V E , excess molar enthalpies, H E , excess Gibbs free energies, G E and excess isentropic compressibilities, Ä E S data of binary [1][2][3] and ternary [4,5] mixtures have been analyzed in terms of Graph theory (which involves the topology of a molecule). In continuing with our study on thermodynamic properties of cyclic mixtures, we report here the densities, speeds of sound and excess…”
Section: Introductionmentioning
confidence: 99%